Characteristics of pregnant women at risk and relationship with type of delivery and complications - Marina de Góes Salvetti; Luciana Garcia Lauretti; Roseni Carvalho Muniz; Thalyne Yuri Souza Farias Dias; Amanda Aparecida Duarte Gomes de Oliveira; Luciana Magnoni Reberte Gouveia (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to describe characteristics of pregnant women at risk and analyze the relationship with type of delivery and complications during pregnancy and puerperium. Methods: a retrospective study with secondary data of 1,574 at-risk pregnant women followed up in an educational intervention by telemedicine. Results: pregnant women with an average age of 35 years and high educational level participated. Preference for normal delivery was 43.1%, but only 17.3% had normal delivery. During pregnancy, 43.5% sought emergency care. In the postpartum period, 2.0% needed an ICU. Emergency room search was associated with age and contacts with the intervention. Cesarean delivery was associated with age, physical inactivity and overweight/obesity. ICU admission was associated with age and BMI. Conclusion: pregnant women were of high age and education, the younger and who had more contacts with the intervention sought more the emergency room. Older age, physical inactivity and overweight/obesity were factors associated with cesarean delivery.